Konsep Pembaharuan Pendidikan Islam Perspektif Muhammad Rasyid Ridha - zakoni, muhammad zakoni; Sahroni, Ervi (Tarbawi, 2023)
Islamic education in Indonesia is generally still traditional. The curriculum used in various Islamic educational institutions is still in a dichotomous model between religious knowledge and general science. Teaching is still based on mastery of the material through an all-verbalistic rote system. namely being able to say but do not understand its purpose, let alone practice it. In reality, Islamic education has not been able to instill Islamic values ​​in students which has led to a decline in morale among students. Through Muhammad Rasyid Ridha's thoughts, it is hoped that there will be renewal in the implementation of Islamic education in a better direction. The problem in this research is how to renew Islamic education from Muhammad Rasyid Ridha's perspective. This study aims to identify, describe and analyze the renewal of Islamic education from the perspective of Muhammad Rasyid Ridha in order to obtain a complete picture related to educational reform. This study uses a qualitative descriptive method using content analysis. The results of this study are that renewal in Islamic education is the answer to the rapid development of the times in the era of globalization, especially with the sophistication of Science and Technology (IPTEK) which must be adapted to Faith and Taqwa (IMTAQ). The renewal of Islamic Education offered by Muhammad Rasyid Ridha to Islamic education aims to produce pious, independent, and advanced human beings in various fields of life, as well as curriculum.